Teacher Competency in Practicing Inclusive Education: A Systematic Review - Rapisa, Dewi Ratih; Hermanto, Hermanto; Suparno, Suparno (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Dealing with the diverse characteristics and learning needs of learners in inclusive learning is one of the main challenges of education today. Teacher competency in inclusive education plays a critical role in addressing these challenges. This systematic review, conducted using the PRISMA method, analyzed literature from Scopus, PubMed, and Web of Science (WoS) databases published between 2020 and 2024. A total of 1,237 articles were initially identified, and after applying inclusion and exclusion criteria, 21 articles were selected for analysis. The review found that core competencies in professional knowledge, classroom management, and differentiated teaching are essential for effective inclusive education. Positive teacher attitudes toward inclusion and self-efficacy significantly influence the success of inclusive practices, particularly in countries such as Indonesia, Mauritius, and South-Central Vietnam. Challenges identified include insufficient training, large class sizes, and a lack of specialized support, all of which hinder the implementation of inclusive strategies. Recommendations for improving teacher competencies include enhancing collaboration between general and special education teachers, providing ongoing professional development, and integrating technology. The findings emphasize the need for tailored training programs, self-assessment tools like the Self-Assessment of Inclusive Skills (SAIS), and the development of competency-based teacher education (CBTE) models to enhance inclusive teaching practices.